William Stillman, Rhode Island Mechanician and Communicator—His Lock Patents and Acrostics - Brockmann, R. John (Journal of Technical Writing and Communication, 1996)
Focusing only on the famous and celebrated has skewed military and political history; focusing only on Oliver Evans, Lauchlan McKay, John W. Griffiths, Joseph Crane, and John H. Patterson could similarly skew our sense of American technical communication in the nineteenth century. Exploring the written work of an ordinary American mechanician of the nineteenth century, William Stillman of Rhode Island, could help balance our appraisal of nineteenth-century American technical communication. Reviewing the writing and graphics in his 1851 Miscellaneous Compositions, as well as his 1839 lock patent and 1836 bank lock instructions, reveals Stillman's ambidextrous abilities in using both text and graphics to communicate; abilities similar to his more famous fellow citizens. However, the three-dimensional qualities of his 1839 patent graphic reveals an unusual ability to mimic the biological methods in which the human eye sees three dimensions.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjE5MC9hNDM0LTllYmYtdW1jZS04ZDhu